USE OF QUALITY TOOLS ISHIKAWA DIAGRAM AND FMEA - ANALYSIS OF MODES AND EFFECTS OF FAILURES IN COMPANIES - Silva, Isabela Moreira; Casagrande, Diego José (Revista Interface Tecnológica, 2022)
Quality is more evident every day, as it is not limited to the adjective of a product or service, it is much more than that. Quality can be seen as a Management System, as Quality Tools, as synonymous with efficiency. In terms of methodology in this research, a systematic review of the literature was carried out, where the application of the FMEA Quality tools - Failure Modes and Effects Analysis and Ishikawa Diagram in companies from different segments and the positive results they had using these tools. At the end of the research, it can be concluded that the application of these quality tools has the characteristic of "being worked together" with other tools, which consequently has positive results and makes them always used. In addition to being easy to apply tools that provide a lot of valuable information for companies.
Keywords: FMEA; Ishikawa Diagram; Quality Tools